The Effect of Pre-season Training and Early Competitive Period on Haematological, Skeletal Muscle and Physiological Markers in Starters and Non-starters Greek Professional Soccer Players - Volianitis, Στέφανος; Bakas, Γεώργιος; Manouras, Νικόλαος; Flouris, Ανδρέας Δ.; Famisis, Κωνσταντίνος (Inquiries in Physical Education and Sport, 2019)
Metabolic responses to training in soccer depend on the combined physiological stress of pre-season training and official games. The purpose of the present study was to monitor the metabolic changes during the pre-season and first competitive mesocycle by measuring haematological and physiological parameters in soccer players with and without playing action. Twenty-one professional players, split into starters (n=10) and non-starters (n=11) having played in >75% and <25% of the total game time (7 games), respectively, participated in the study. Blood samples were collected at the start of the preparation (July), before the first official game (September) and at the end of the first competitive mesocycle (November), and analyzed for haematocrit, haemoglobin, urea, creatine kinase (CK), aspartate aminotransferase (AST), alanine aminotransferase (ALT), iron, ferritin, free testosterone and cortisol. VO2max and running velocity at 4 mM lactate (V4) were measured in July and September. Heamoglobin and haematocrit increased during the pre-season (13.98 vs. 14.29 g/dL, p=.024 and 41.51 vs. 42.55 %, p=.005; respectively) and rose further during the early competitive season (14.68 g/dL, p=.001 and 43.87 %, p<.001; respectively). Urea, CK and AST increased (p<.05), while ferritin decreased (p<.05) during the pre-season. Testosterone increased (p<.05) during the competitive mesocycle, while there was no change in ALT and cortisol. Starters had lower urea (31.77 vs. 36.90 mg/dL, p=.016) and iron (77.7 vs. 92.8 μg/dL, p=.029) but higher ferritin (p<.05), VO2max and V4 compared to non-starters (56.6 vs. 53.9 ml O2/kg/min, p<.001, and 13.4 vs. 12.7 km/h, p=.02; respectively). In conclusion, during the pre-season there was evidence of catabolism that reversed to anabolism during the first competitive mesocycle and starters had higher physical fitness parameters compared to non-starters.